COOPERATIVE PRINCIPLE IN PARMOEDYA ANANTA TOERS’ NOVEL BUMI MANUSIA - M. Rawi Bintoro; M. Manugeren; Devi Pratiwy (Universitas Islam Sumatera Utara, 2022)
People always do communication with others. Communication has several functions, such as conveying idea and giving information to others. In conveying idea and giving information, people use a language. One main requirements needed by person to do communication is to make sure that the listener or people involved in the conversation will cooperate each other; so by this, the communication can run well. Paul Grice states that the cooperative principle is the assumption that participants in a conversation normally attempt to be informative, truthful, relevant, and clear and the cooperative principle of conversation is elaborated in four sub-principles called maxims. They are maxim of quantity, maxim of quality, maxim of relevance and maxim of manner. The aims of this study are to reveal the use of framework principle and to entangle the implied meanings in the conversations in terms of their maxim arrangement. This research uses descriptive qualitative method and the results show that there are maxim of relevant, quality, quantity and manner used in the novel.